The Role of Antiviral Therapy for HBV-Related Hepatocellular Carcinoma - Liang-He Yu; Nan Li; Shu-Qun Cheng (International Journal of Hepatology)
Hepatocellular carcinoma (HCC) is a highly prevalent and lethal cancer worldwide; despite the curative treatment for HCC, the rate of tumor recurrence after hepatectomy remains high. Tumor recurrence can occur early (<2 years) or late (>2 years) as metastases or de novo tumors. Several tumor factors were associated with HCC recurrence; high hepatitis B virus (HBV) load is the major risk factor for late recurrence of HCC after resection. Preoperative antiviral therapy improves liver function, and postoperative reduce HCC recurrence. In this paper, we focus on antiviral treatment to improve the liver function, prevent recurrence, and lengthen the overall survival for HBV-related HCC.